PHARMACEUTICAL MANAGEMENT IN HEALTHCARE WITH THE ORGANISATION OF THE HEALTHCARE SERVICE - Jovanović, Dražen; Nikolić, Milan (ACADEMIC REVIEW, 2018)
Health management is a process of managing all aspects of the health system in order to improve public health, while pharmaceutical management represents the process of managing all aspects of diagnosis and treatment of patient illness through the development and application of medicines. They are based on finding the best solutions using limited resources, and are implemented through planning, organizing, guiding and control activities.Pharmaceutical management in healthcare can only function properly if it has a good organization. The priority of pharmaceutical management in healthcare should be proper drug supply and proper drug access management policies and other healthcare technologies.